Rancang Bangun Mesin Pencetak Batu Bata Dengan Sistem Ekstrusi - Yuliarman Yuliarman; Aidil Zamri; Asmed Asmed (Jurnal Teknik Mesin, 2004)
Amount of resident of Indonesia progressively mount and it is of course require construction material for the requirement of its housing. Construction material which is partly produced by small industry or home industry. One of the production construction materials is brick. At the moment requirement to brick product very is mounting, for that need the existence of support in the form of availability of a machine able to improve productivity in line with make-up of its requirement. System of extrusion which is used in machine printer of brick can improve small industrial productivity brick to requirement of construction material market.